دراسة حول العلاقة بين تأثير الحقول الكهرطيسية وأخطار الإصابة بسرطان الثدي لدى النساء. - يحيى سليمان; مدحت سعيد (Tishreen University, 2016)
We prove in the following study, the physical mechanism of the EMF effects produced by the electric blankets and beds , on the nervous cells, and its relation with risks of breast cancer on women. Sensitivity of the melatonin compound to the EMF and its variation rates on that risks, are also studied. This study indicates the decrease of the rate of that compound with the absorbed EMF doses with time, due to the pineal gland sensitivity to the EMF (which is the main center of melatonin production) . We used the Scanning Electron Microscope (S.E.M) to show the H-ions and the free radicals formation from some DNA compounds . نبين في الدراسة التالية الميكانيكية الفيزيائية لتأثير الحقول الكهرطيسية الناتجة عن الحرامات والفرش الكهربائية على الخلايا العصبية ومدى ارتباط استعمالها بخطر الإصابة بسرطان الثدي لدى النساء. تمت دراسة تحسس مُرَكَّب الميلاتونين لشدة تأثير الحقولEMF وتأثير تغير نسبه على مقدار تلك الإصابة. تشير هذه الدراسة الى انخفاض نسبة ذلك المركب مع تراكم جرعات EMF مع الزمن ، نظراً لتحسس الغدة الصنوبرية نتيجة تعرضها لتأثير تلك الحقول مع الزمن ، اذ تمثل أو تعتبر تلك الغدة المركز الرئيسي لأنتاج ذلك المركب. تم استخدام المجهر الالكتروني الماسح (S.E.M) لاثبات تشكل الجذور الحرة وأيونات الهيدروجين عند استخدام أحد القواعد الأساسية لمركب DNA